PENGARUH KOMPETENSI APARATUR, SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN ASISTENSI KEUANGAN SEBAGAI VARIABEL MODERASI ( Studi pada Pemerintah Kabupaten Intan Jaya ) - Kawer, Deddy A.; Hafizrianda, Yundy; Kambuaya, Maylend K. P (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
This research aims to examine the influence of apparatus competency and internal control systems on the quality of financial reporting. As well as testing the influence of apparatus competency and internal control systems on the quality of financial reporting which is moderated by financial assistants in the Intan Jaya Regency government. The independent variables used are the influence of Apparatus Competence, Internal Control System. The moderating variable is financial assistance, while the dependent variable is the quality of financial reporting. The sample for this research is people who are employees who have authority in the field of accounting or finance, totaling 83 respondents. The analytical tool in this research uses SPSS 23. This type of research is causality, namely testing the influence of independent variables on the dependent so that researchers use Moderation Regression Analysis (MRA). So the results of this research must meet the Classical Assumption Test, namely the Normality Test, Multicollinearity Test and Heteroscedesity Test. The results of this research partially show that Apparatus Competence and Internal Control Systems have an influence with significance values of 0.000 and 0.000 respectively. Meanwhile, Financial Assistance was unable to moderate the influence of Apparatus Competency and Internal Control Systems on the Quality of Financial Reporting with respective significance values of 0.857 and 0.147